Study on Energy Conversion Efficiency and Structure Optimization of the Multorifices Nozzle for Radial Jet Drilling - Famu Huang; Ziheng Zhu; Jian Wang; Ping Zhang; Zhongxin Ren; Jun Lu; Haibo Su; Hong Zhang; Jingbin Li (Geofluids)
Underground gas storage (UGS) is a crucial method for mitigating seasonal fluctuations in natural gas consumption. However, in China, UGS is primarily achieved through the conversion of abandoned gas reservoirs with limited storage capacity. Radial jet drilling (RJD) is an effective technology for the secondary development of depleted reservoirs. The multiorifice nozzle is a critical component that can efficiently break rock and create radial holes to increase gas production. In this study, we investigate the impact of nozzle structure on energy conversion efficiency through numerical simulations and experiments. Additionally, we design a swirling multiorifice nozzle and verify its effectiveness in field applications. Our findings indicate that the nozzle pressure drop and vorticity are primarily generated at the acute angle of the orifices. The number of forward orifices is directly proportional to energy loss, while the discharge coefficient and hydraulic performance initially increase and then decrease. Swirling multiorifice nozzle have fewer backward orifices, so they have less energy loss and a larger discharge coefficient. It has achieved better rock-breaking results in field applications. In conclusion, this study provides theoretical guidance and technical support for the secondary development of gas storage.